Bilanggo (Prison No. 10069) - Fernandez, Eddie; Romero, Chanda; Bautista, Beth; Saez, Nilo; Mirick Films international (Firm). ([Place of production not identified] Mirick Films International, 1982)
The real-life experiences behind bars of actor Eddie "Lagalag" Fernandez are depicted in this action-drama movie--https://www.imdb.com/title/tt0465918/?ref_=fn_al_tt_4
Music by Tito Sotto; cinematography by Armando De Guzman.
Eddie Fernandez, Chanda Romero, Beth Bautista.
DVD
In Tagalog
Keywords: Action; Drama